Understanding Normative and Historical Islamic Approaches in Islamic Studies: Islamic Religious Education Studies - Miftahul Ihsan; Sabarudin Sabarudin (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to explore the role of Islamic values, both normative and historical, in shaping adolescent identity. Normative Islamic values, which are based on religious teachings, and historical Islamic values, which reflect the cultural heritage and long history of Islam, have a significant impact on adolescents' self-understanding, behavior and worldview. In a normative approach, this research highlights how values such as faith, worship and Islamic ethics shape teenagers' religious identity. The library research research method is used to explore and analyze normative and historical approaches in Islamic studies, and a qualitative approach with content analysis is used to analyze and present research findings. The research results show that understanding and internalizing these values influences a strong religious identity in adolescents. In addition, Islamic moral and ethical concepts, such as justice and goodness, influence teenagers' behavior in everyday life. On the other hand, in a historical approach, this research emphasizes that historical Islamic values play a role in shaping the cultural and social identity of adolescents. These values reflect the cultural and historical heritage of Islam, influencing adolescents' cultural identity and worldview